Cyber Public Relations Crisis experienced by Holywings Indonesia - Maudy Marditta Putridinanti; Eka Angeliani Putri; Taufiqur Rahman; Iren Sadeva Azhar (Jogjakarta Communication Conference (JCC), 2023)
Cyber ​​Public Relations as a new place for companies to show their best image through media that is familiar to the community. However, in this case study, Holywings made a mistake in creating content which ultimately violated several Cyber ​​Public Relations codes of ethics which alluded to SARA elements. The brand image that has been built since the beginning of pioneering must be destroyed and get a bad image by the public due to the handling of the crisis which is felt to be irresponsible for the chaos that has occurred in the public eye. through a case study approach and a qualitative-method the authors conducted an analysis of violations of the cyber public relations code of ethics and the handling that should be carried out by companies when facing a crisis.